(untitled) (Bangladesh Journal of Child Health, 2012)
Children are most susceptible to accidental exposure of common household substances and one of the common household substances is nail polish remover. The chemical N,N-dimethyl-p-toluidine is a chemical commonly found in artificial fingernail solutions. Its oxidation metabolite phenylhydroxylamine is presumably one of the most potent chemical producers of methemoglobin. Fingernail care products account for a significant number of pediatric poisonings in the western world with few fatalities. We are presenting a case of accidental ingestion of nail polish remover with lethal Methemoglobinemia (Serum methemoglobin level-72%). This patient was treated successfully with injection methylene blue. However, even small amounts can be dangerous to children, so it is important to keep this and all household chemicals in a safe place. DOI: http://dx.doi.org/10.3329/bjch.v36i1.13040 Bangladesh J Child Health 2012; Vol 36 (1): 49-50